2004
DOI: 10.1186/1471-2407-4-6
|View full text |Cite
|
Sign up to set email alerts
|

HFE C282Y and H63D in adults with malignancies in a community medical oncology practice

Abstract: Background: We sought to compare frequencies of HFE C282Y and H63D alleles and associated odds ratios (OR) in 100 consecutive unrelated white adults with malignancy to those in 318 controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
(67 reference statements)
1
11
0
1
Order By: Relevance
“…C282Y mutation carrier rate was not significantly elevated in ET patients (16.2%), compared with controls (10.2%). Barton et al (20) evaluated 100 consecutive unrelated Caucasian adults with malignancy in a community medical oncology (21) found similar HFE allele frequencies (2.2% for C282Y and 11.5% for H63D) among 52 patients with PV to that found in a previous study reporting on normal Italian population. In contrast to previous HFE epidemiologic studies, where HFE C282Y or H63D were found to be a potential risk factor in carcinogenesis, in the present study, decreased C282Y allele frequencies were found in a large CMPD patient cohort compared with healthy blood donors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…C282Y mutation carrier rate was not significantly elevated in ET patients (16.2%), compared with controls (10.2%). Barton et al (20) evaluated 100 consecutive unrelated Caucasian adults with malignancy in a community medical oncology (21) found similar HFE allele frequencies (2.2% for C282Y and 11.5% for H63D) among 52 patients with PV to that found in a previous study reporting on normal Italian population. In contrast to previous HFE epidemiologic studies, where HFE C282Y or H63D were found to be a potential risk factor in carcinogenesis, in the present study, decreased C282Y allele frequencies were found in a large CMPD patient cohort compared with healthy blood donors.…”
Section: Discussionsupporting
confidence: 61%
“…The S142G variant of TFR was reported to influence cancer susceptibility (colon, breast, myeloma) in combination with distinct HFE genotypes (13). The effects of iron homeostasis, and HFE and TFR genotypes were extensively studied in several solid tumors even in large patient cohorts (7)(8)(9)(10)(11)(12)(14)(15)(16)(17)(18)), but only a few studies with small patient cohorts tested the potential role of HFE in chronic myeloproliferative disorders (CMPD), a clonal disorder of the main iron using tissue of the body (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…1,19,26,[31][32][33][34][35] Patients with hemachromatosis have an increased incidence of cirrhosis, hepatocellular carcinoma and some other malignancies. [35][36][37][38][39][40] Similarly, CLD is one of the major long-term complications in HSCT survivors. Whereas Strasser et al, 4 reported a cumulative incidence of CLD in 3.8% by 20 years after transplantation in a series of 3721 patients, Tomas et al, 6 reported CLD in 57.5% of their cohort of 106 patients in 2 years follow-up, which strongly correlated with siderosis.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Given that the frequencies of the alleles in the Jewish population are in Hardy-Weinberg equilibrium, double heterozygosity for H63D and ␤-thalassemia is expected in more than 1/200 individuals from these ethnic groups, and homozygosity for the first, with heterozygosity for the second, is expected in more than 1/3200 individuals from these groups. In view of side effects associated with iron overload, such as hepatocellular carcinoma, 35 other cancers, 36 and immunodeficiency, 37 iron body stores should be assessed and genetic evaluation performed in these Jewish populations when required. This information has significance for preventive and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%